Algonquin materials, Indian manuscripts, 1661-1879 - Depéret, Élie, 1691-1757; Chaumonot, Pierre Joseph Marie, 1611-1693; Mathevet, Jean Claude, 1717-1781; Cuoq, J. A. (Jean André), 1821-1898; Gay (Guay), Robert-Michel, 1663-1725; Quéré de Tréguron, Maurice, 1663-1754; Guichart, Vincent-Fleuri, 1729-1793 (1661)
These manuscripts include dictionaries, grammars, catechisms, prayers, canticles, hymns, and Bible tales prepared by French Sulpician missionaries in New France in Algonquin, the Nipissing dialect of Algonquin, and some Iroquoian languages. From originals at the Seminaire de Montreal, les Pretres de Saint-Sulpice.